2011
DOI: 10.2478/v10237-011-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

Examining Biomechanical and Anthropometrical Factors as Contributors to Iliotibial Band Friction Syndrome

Abstract: Examining Biomechanical and Anthropometrical Factors as Contributors to Iliotibial Band Friction Syndrome This study was conducted in an attempt to determine if the biomechanical parameters thought to predict iliotibial band injury could accurately differentiate between iliotibial band (IT band) injured and healthy runners. 20 injured and 20 healthy runners were tested. Injured subjects were randomly assigned into groups of ten (INJ-1 or INJ-2). Ten healthy runners acted as controls (CON) and ten healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Greater knee internal rotation in the ITBS group was determined to be caused by greater external femoral rotation, while internal tibial rotation was lower than the controls. Bauer & Duke (2012) also reported a lack of excessive internal tibial rotation in individuals with ITBS. Excessive external femoral rotation can be caused by muscular imbalances at the hip.…”
Section: Kinematics Of Itbsmentioning
confidence: 91%
See 1 more Smart Citation
“…Greater knee internal rotation in the ITBS group was determined to be caused by greater external femoral rotation, while internal tibial rotation was lower than the controls. Bauer & Duke (2012) also reported a lack of excessive internal tibial rotation in individuals with ITBS. Excessive external femoral rotation can be caused by muscular imbalances at the hip.…”
Section: Kinematics Of Itbsmentioning
confidence: 91%
“…To avoid heel strike occurring while the ITB is in the impingement zone, sprinting has been determined to help individuals recover from ITBS because an individual lands with more knee flexion and thus the ITB has moved past the impingement zone by the time heel strike occurs (Orchard et al, 1996). However, this is not supported by researchers who found that ITBS patients had increased knee flexion at heel strike while running (Miller et al, 2007;Bauer & Duke, 2012).…”
Section: Extrinsic Factors Contributing To Itbsmentioning
confidence: 99%